PSYCHOLOGICAL ASPECTS OF SELF-HARMING BEHAVIOR IN YOTH DEPRESSIONS - Enikopov , S. N.; Medvedeva , T. I.; Vorontsova, O. Yu.; Kazmina , O. Yu. (Modern Psychology, 2019)
The article presents the results of the analysis of psychological features of depression patients with self-injury. The study involved 42 patients with depression, 23 of them with self-injury. The methods used include: Wisconsin Card Sorting Test, Iowa Gambling Task (IGT), Implicit Associations Test (IAT), SCL-90-R, Hamilton Depression Rating Scale, Rosenberg self-esteem scale, Body Investment Scale (BIS). It was shown that suicidal risk parameters were elevated for the group with self-injury; motor and ideator inhibition was less pronounced, while the affective component was significantly more pronounced; higher sensitivity may cause vulnerability to experiencing acute mental pain; significance of bodily symptoms was reduced with elements of body experience dissociation.